Pengaruh Pemberian Tepung Ikan Tongkol Dalam Ransum Terhadap Recahan Karkas Ayam Kampung Super Umur 10 Minggu - I Kadek Wira Parwata; I Gusti Agus Putra Sanjaya; Luh Suariani (GEMA AGRO, 2025)
Livestock in Indonesia is currently experiencing very rapid development. One source of protein, especially native chicken. Super native chicken requires quality feed to fulfill its nutrition in order to obtain optimal results. Feed ingredients that need to be utilized as alternative feed ingredients include those from fishery slaughterhouse waste, such as skipjack tuna waste. The purpose of this study was to determine the effect of providing skipjack tuna waste flour on carcass fractures of 10-week-old super native chicken. The experimental design used was a Completely Randomized Design (CRD) consisting of 5 treatments and 3 replications. The results showed that there was no significant difference (P>0.05) in chest and back weight, Therefore, further research is needed to evaluate the utilization of tuna fish waste flour at a level higher than 12%, in order to determine the optimal limit of its use in supporting chicken growth efficiently and economically.